Digital Creativity Based on Local Wisdom: Creating Science Audio Comics for Science Teachers Using Canva and AI - Suriyah Satar; Ricky Engel Mawara; Mustika Irianti; Cartika Candra Ledoh; Nurbaya, Nurbaya; Hanida Listiani; Ramadani Widi Permadi; Grand Barrang; St. Rahmadani (CV. Creative Tugu Pena, 2025)
This community service program was designed to empower science teachers in Keerom Regency, Papua, through the development of audio comics based on local ethnography, utilizing Canva and Artificial Intelligence (AI) as digital tools. The program specifically aimed to integrate Papuan cultural narratives into science learning, thereby creating contextualized and culturally relevant instructional materials for students. A total of 35 science teachers, organized under the MGMP IPA (Subject Teachers Forum), participated in the program. The method employed a participatory workshop model, followed by sustained coaching and evaluation. Teachers were trained to design digital comics using Canva, generate illustrations and voice-overs with AI tools, and embed local cultural stories such as traditional hunting, forest management, and local folklore into science topics like ecosystems, energy cycles, and adaptation of living organisms. The process included pre-test and post-test assessments, hands-on production of audio comics, classroom trials, and the establishment of a digital repository for documentation and dissemination. The findings revealed a 33% increase in teachers’ digital literacy across three assessed domains: mastery of Canva and AI tools, integration of culture into science content, and pedagogical competence in developing audio comics. Five audio comics were fully developed and ready for classroom use, while 28 were in progress. Classroom trials demonstrated enhanced student engagement, improved comprehension of abstract science concepts, and stronger connections between cultural knowledge and scientific understanding. Overall, this program demonstrates that combining digital technologies with local ethnography is an effective approach to empower teachers, enrich science learning, and promote educational innovation in underserved regions such as Papua.